2021
DOI: 10.3389/fphar.2021.750031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Almonertinib Crossing the Blood-Brain Barrier in EGFR-Mutant NSCLC Brain Metastasis and Spinal Cord Metastasis Models

Abstract: Roughly one third of non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI)-sensitive mutated (EGFRm) tumors experience disease progression through central nervous system (CNS) metastases during treatment. Although EGFR-TKIs have been reported to be favored in some patients with EGFRm NSCLC CNS metastases, novel EGFR-TKIs with proven efficacy in CNS pathologies are clinically needed.To investigate whether almonertinib, a novel third-generation EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…These results indicate that aumolertinib is an effective third-generation EGFR TKI for patients with EGFR T790M-positive advanced NSCLC after disease progression following first- and second-generation EGFR TKI therapy ( 17 ). In the mouse model of NSCLC brain and spinal cord metastases, aumolertinib easily penetrates the blood-brain barrier and inhibits brain and spinal cord metastases ( 18 ). In the AENEAS study, aumolertinib, as a first-line treatment for locally advanced or metastatic EGFR-mutated NSCLC, achieved a PFS time of 19.3 months, which is marginally higher than the time of 18.9 months achieved with osimertinib in the FLAURA study ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that aumolertinib is an effective third-generation EGFR TKI for patients with EGFR T790M-positive advanced NSCLC after disease progression following first- and second-generation EGFR TKI therapy ( 17 ). In the mouse model of NSCLC brain and spinal cord metastases, aumolertinib easily penetrates the blood-brain barrier and inhibits brain and spinal cord metastases ( 18 ). In the AENEAS study, aumolertinib, as a first-line treatment for locally advanced or metastatic EGFR-mutated NSCLC, achieved a PFS time of 19.3 months, which is marginally higher than the time of 18.9 months achieved with osimertinib in the FLAURA study ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, novel EGFR-TKIs with proven efficacy in CNS are clinically needed. Pharmacokinetic studies in mice showed that almonertinib, a novel third gen TKI, has a good BBB penetration ability [232], and early clinical evidence of almonertinib activity in a patient with advanced EGFRm NSCLC and BMs has been reported, showing intracranial and extracranial response [232].…”
Section: Open Questions In Treatment Strategiesmentioning
confidence: 99%
“…107,118,119 In contrast, the third-generation EGFR-TKIs osimertinib, almonertinib, and lazertinib have good bloodbrain barrier penetration. [120][121][122] Compared with first-generation EGFR-TKIs, upfront osimertinib resulted in improved CNS outcomes. 119 These data support osimertinib as upfront treatment in this setting.…”
Section: Systemic Treatment Of Nsclc Brain Metastasesmentioning
confidence: 99%